ESports competition as an novation of information society and methodology of its design - D. V. Kravchenko; I. V. Bel’skij; V. P. Starzhinskij (Системный анализ и прикладная информатика)
ESports are considered as novation of the information society. The quality of an eSports competition as a process providing an information-to-technological service is defined. The need to develop the technical-to-technological component design techniques of eSports competitions and their implementation in the frame of QMS ISO 9000 is justified.